Charles Tilly: Legado y estela De The Vendée a Contentious Performances, para comprender el conflicto político del s. XIX español - Martínez Dorado, Gloria; Iranzo, Juan M. (Política y Sociedad, 2010)
Charles Tilly’s later work sums up, assesses, specifies and projects into the future the theoretical and empirical legacy of a life of study devoted to Historical Sociology. From his masterpiece opera prima, The Vendée, on to his latest Contentious politics, Tilly developed a vast array of theoretical concepts, which he provided with extensive and precise empirical referents (among them, we may cite: performance, collective action repertoire, political opportunity structure, mechanisms for mobilization and, finally, worthiness, unity, numbers and commitment). Today, these notions are located at the very core of the sociological/historical studies about political contention in early Modern Europe. Tilly’s preference for quantitative and comparative methods was subservient to his interest in giving account of, not the motivational Why?, but the objective How, When and What for of collective mobilization; not in explanatory ‘laws’ of historical change, but in analytically fecund descriptions of similar, but also unique historical episodes. This article adopts the methodological paradigm Tilly first developed when writing The Vendée, analytically updated throughout his later work, as theoretical framework for a new approach of the social and political mobilization that led to the first Carlista war. Specifically, the mechanisms for mobilization that provided material and human resources for the war effort are researched in three different Navarre villages –selected by their differing economic, cultural, and politically features.
Keywords: Charles Tilly; Contentious politics; Performance; Collective action repertoire; Political opportunity structure; Mechanisms for mobilization; WUNC display; La Vendée; Carlism; Civil war; First Carlista war